2010
DOI: 10.1007/s00296-010-1451-0
|View full text |Cite
|
Sign up to set email alerts
|

A case report of systemic lupus erythematosus combined with Castleman’s disease and literature review

Abstract: Although lymph node enlargement is common in active systemic lupus erythematosus (SLE), lymph node examination is frequently ignored in the diagnosis of SLE. Clinical presentation and abnormal laboratory findings are often sufficient for SLE diagnosis, not to mention that the specific histological finding of lymph node necrosis in SLE is rarely seen, and the follicular hyperplasia is usually considered as nonspecific. However, since the late 1990s, a few cases of SLE lymphadenopathy have been reported exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
8
0
3
Order By: Relevance
“…In the unicentric form of the disease, surgical resection is often curative (Talarico et al, 2008), whereas M-CD treatment is more difficult and includes steroids, chemotherapy or radiotherapy (Asgarani et al, 2006), antiviral drug, and monoclonal antibodies. Xia et al (2012) reported a case of SLE combined with CD in a 23-year-old girl who displayed systemic symptoms, including systemic lymphadenopathy and abnormal laboratory findings, indicating the active phase of SLE. Xia et al (2012) reported a case of SLE combined with CD in a 23-year-old girl who displayed systemic symptoms, including systemic lymphadenopathy and abnormal laboratory findings, indicating the active phase of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In the unicentric form of the disease, surgical resection is often curative (Talarico et al, 2008), whereas M-CD treatment is more difficult and includes steroids, chemotherapy or radiotherapy (Asgarani et al, 2006), antiviral drug, and monoclonal antibodies. Xia et al (2012) reported a case of SLE combined with CD in a 23-year-old girl who displayed systemic symptoms, including systemic lymphadenopathy and abnormal laboratory findings, indicating the active phase of SLE. Xia et al (2012) reported a case of SLE combined with CD in a 23-year-old girl who displayed systemic symptoms, including systemic lymphadenopathy and abnormal laboratory findings, indicating the active phase of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 En 1978 se publicaron casos con manifestaciones sistémicas que presentaban linfadenopatía generalizada periférica, hepatoesplenomegalia, fiebre, diaforesis y nódulos linfáticos con célu-las plasmáticas, actualmente conocida como variante multicéntrica de células plasmáticas, siendo relacionada a enfermedades autoinmunes del tejido conectivo. 3,4,5 Las variables histopatológicas de la enfermedad de Castleman son la de tipo hialino vascular, la de células plasmáticas y la mixta. Por su localización, pueden clasificarse en unicéntrica y multicéntrica, siendo esta última asociada a infecciones como herpes virus tipo 8 y virus de inmunodeficiencia adquirida.…”
Section: Introductionunclassified
“…7,8 Durante el estudio histopatológico del nódulo linfático, la reducción de células CD-57 positivas en los centros germinales y un aumento de células dendríticas CD-21 positiva en la zona de manto, dan soporte al diagnóstico de enfermedad de Castleman, tal como se evidencia en el presente caso donde la inmunomarcación dio positiva para células dendríticas con CD-21 positiva. 5 El tratamiento quirúrgico realizado con la extirpación del tumor, permitió la resolución sintomática en un tiempo relativamente corto, reflejando como probable causa de la polimiositis a la enfermedad de Castleman. Los tratamientos enfocados en la polimiositis idiopática primaria, en donde los tiempos de recuperación suelen de semanas a meses, a diferencia de los casos en que son variante unicéntrica, al ser diagnosticado antes o durante el desarrollo de una enfermedad autoinmune conlleva generalmente a una mejoría sintomática en corto tiempo.…”
unclassified
See 1 more Smart Citation
“…CD is a heterogenous group of lymphoproliferative disorders characterized by a hyperplastic-reactive process involving the immune system. CD complicated with SLE is a rare clinical condition with only a few cases[ 1 2 3 ] reported. Although autoimmune thrombocytopenia (AITP) was seen in nearly 50% of these patients, the severity was mostly mild to moderate, while severe thrombocytopenia at the onset of disease (before chemotherapy) has not been previously reported.…”
mentioning
confidence: 99%